Destinasi Mice: Kota Depok Sebagai Destinasi Alternatif Mice di Jawa Barat - Yustisia Pasfatima Mbulu; Yosi Erfinda; Fetty Nurmala Rossi (Tourism Scientific Journal, 2021)
This study aims to map the existing conditions of MICE (Meeting, Incentive, Convention, Exhibition) destinations in Depok City, analyse the attributes of MICE destinations in Depok City as an alternative to MICE destinations in West Java, and formulate a strategy for developing MICE destinations in Depok City in West Java. The research method used is descriptive qualitative with field data surveys or direct observation to the city of Depok. As well as interviews with EOs, hotels, malls, and the Department of Youth, Sports, Culture and Tourism. The results obtained from the MICE destination components have been fulfilled, all of which only need improvement from the aspects of MICE accessibility, MICE attractions and HR. Meanwhile, the attributes of MICE destinations in Depok City as an alternative MICE destination in West Java have been fulfilled. Everything needs to improve accessibility, extra opportunities, information, meetings, accommodation facilities and meeting facilities. Based on calculations using the SWOT approach, the City of Depok as an alternative destination for MICE in West Java is in the quadrant I position. This shows a very favourable situation for Depok City to carry out aggressive growth/growth. Then the results of the IFE and EFE get the value of strength and opportunity (SO) 5.51, strength and threat (ST) 3.16, weakness and opportunity (WO) 2.9, and weakness and threat (WT) 0, 55. The strategy that has the highest value is SO 5.51.